2014
DOI: 10.1007/s11250-014-0729-8
|View full text |Cite
|
Sign up to set email alerts
|

Breeding objectives for pigs in Kenya. II: economic values incorporating risks in different smallholder production systems

Abstract: This study estimated economic values for production traits (dressing percentage (DP), %; live weight for growers (LWg), kg; live weight for sows (LWs), kg) and functional traits (feed intake for growers (FEEDg), feed intake for sow (FEEDs), preweaning survival rate (PrSR), %; postweaning survival (PoSR), %; sow survival rate (SoSR), %, total number of piglets born (TNB) and farrowing interval (FI), days) under different smallholder pig production systems in Kenya. Economic values were estimated considering two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This study used a data simulation approach to derive an economic value for PY in dairy cattle. Simulation models have been used to predict economic values for traits in the breeding goals for meat sheep (Kosgey et al, 2003), dairy cattle , beef cattle (Rewe et al, 2006) and pigs (Mbuthia et al, 2015) that are produced in the tropics. The model expressed profit through grouping terms by class of cattle and calculated revenue and costs per cow per year.…”
Section: Methodsmentioning
confidence: 99%
“…This study used a data simulation approach to derive an economic value for PY in dairy cattle. Simulation models have been used to predict economic values for traits in the breeding goals for meat sheep (Kosgey et al, 2003), dairy cattle , beef cattle (Rewe et al, 2006) and pigs (Mbuthia et al, 2015) that are produced in the tropics. The model expressed profit through grouping terms by class of cattle and calculated revenue and costs per cow per year.…”
Section: Methodsmentioning
confidence: 99%
“…They face the challenge of the high cost of conventional feed and often resort to the use of locally available feed resources. A survey in Kenya reported that only 30% of pig farmers use commercial feeds while the remaining included some form of alternative feed material in their feeding regime (Mbuthia et al 2014). Mature prosopis pods from Prosopis juli ora tree is such an alternative feed ingredient in Kenya (Kingori et al 2011).…”
Section: Introductionmentioning
confidence: 99%